Evaluation of soaked and unsoaked CBR values of reinforced-soil with coconut husk fibre (CHF) - Tuan Ismail, Tuan Noor Hasanah; Md Madzhar, Mohamad Muazzam Akmar; Yuriz, Yasmin (Applied and Management Sciences Paradigms (IJEAM), 2020)
Recently, soil reinforcement has received more attention due to sustainability, simplicity, and costeffectiveness. The research aimed was to evaluate the efficacy of coconut husk fibre (CHF) in improving the strength properties of laterite soils. A series of laboratory tests such as Atterberg limit test, specific gravity test and hydrometer test was carried out on raw soil. Physical tests were conducted on CHF including density, specific gravity test, and water absorption testing. Geotechnical properties of both unreinforced and reinforced soils were determined through the compaction test and soaked and unsoaked California bearing ratio (CBR) test. The reinforced-soil was prepared by mixing with different ratio of CHF of 0%, 0.25%, 0.50%, 0.75%, 1.00% and 1.50% by mass of dry soil. All unreinforced samples (control samples) are prepared with 0% of CHF. From this research, it had been identified that 0.75% of CHF has the highest CBR value of 27%.